Antoni Cieszyński: a tribute to a savant - Sampath, Prejith; Ahsan, Auswaf; Vengal, Manoj; R, Ashir (Journal of Stomatology, 2020)
The first quarter of the twentieth century, following the discovery of X-rays, was a promising time for radiology. It was a time of experimentation and laid the foundations for the science that brought about a radical change in healthcare. Professor Antoni Cieszyński, a Polish physician, dentist, and surgeon, who worked at the University of Lvov during this period, continues to be remembered for his contribution to dentistry as a whole and oral radiology in particular. The professor, accomplished much during a period that was ridden with strife, in a region that was prone to war, between people of different ethnic origins. Despite the odds, he went on to propose several techniques, across fields as varied as oral radiology, periodontology, and oral and maxillofacial surgery, with some of these techniques still being relevant today. As we pass through a century since the ‘interbellum’, the period between the two world wars, when most of the professor’s works were published, we cannot but forget his contributions to dentistry. This tribute serves as an introduction to his early life, his career achievements, and social activities – an inspiration for all of us to emulate, as the science passes through an era of three-dimensional imaging.